Modulation of optical absorption and electrical properties in Mn-Co-Ni-O-based high-entropy thin films - Ma, Chao (Frontiers in Materials, 2023)
High-entropy thin films of Mn0.6Co0.6Ni0.6Mg0.6Cu0.6O4, Mn0.6Co0.6Ni0.6Mg0.6Zn0.6O4, and Mn0.6Co0.6Ni0.6Cu0.6Zn0.6O4 (MCNMC, MCNMZ, and MCNCZ) with equiatomic proportions were synthesized using chemical solution deposition on silicon substrates. Structural analysis confirmed a consistent face-centered cubic spinel structure, while significant differences in surface morphology were observed. Quantification of the valence states of Mn ions revealed an inverse variation in the concentrations of Mn 4+ and Mn 2+ ions. The heightened infrared light absorption of the MCNMC thin film was assigned to Cu-induced Jahn-Teller distortion and highly polarized Mg-O bonds. All samples exhibited negative temperature coefficient behaviors in their electrical properties. Additionally, the MCNMC thin film demonstrated the lowest resistance due to its denser microstructure, close proximity of Mn 3+ /Mn 4+ ion concentrations, and additional Cu + /Cu 2+ ion pairs, enhancing small polaron hopping conductivity. In contrast, the MCNMZ thin film showed moderate resistance but boasted the highest thermal constant (B25/50) of 3768 K, attributed to its distinctive grain chain structure, facilitating carrier transport while introducing migration barriers.